Seeing the eyes in acquired prosopagnosia. (August 2016) - Pancaroglu, Raika; Hills, Charlotte S.; Sekunova, Alla; Viswanathan, Jayalakshmi; Duchaine, Brad; Barton, Jason J.S.
Abstract: Case reports have suggested that perception of the eye region may be impaired more than that of other facial regions in acquired prosopagnosia. However, it is unclear how frequently this occurs, whether such impairments are specific to a certain anatomic subtype of prosopagnosia, and whether these impairments are related to changes in the scanning of faces. We studied a large cohort of 11 subjects with this rare disorder, who had a variety of occipitotemporal or anterior temporal lesions, both unilateral and bilateral. Lesions were characterized by functional and structural imaging. Subjects performed a perceptual discrimination test in which they had to discriminate changes in feature position, shape, or external contour. Test conditions were manipulated to stress focused or divided attention across the whole face. In a second experiment we recorded eye movements while subjects performed a face memory task. We found that greater impairment for eye processing was more typical of subjects with occipitotemporal lesions than those with anterior temporal lesions. This eye selectivity was evident for both eye position and shape, with no evidence of an upper/lower difference for external contour. A greater impairment for eye processing was more apparent under attentionally more demanding conditions. Despite these perceptual deficits, most subjects showed a normal tendency to scan the eyes more than the mouth. We conclude that occipitotemporal lesions are associated with a partially selective processing loss for eye information and that this deficit may be linked to loss of the right fusiform face area, which has been shown to have activity patterns that emphasize the eye region.